Students’ Career Anxiety: A Systematic Literature Review - Atikah, Denisa Nurul; Kurniawati, Farida; Rifameutia, Tjut (Jurnal Pendidikan Progresif, 2023)
Students’ career anxiety: A systematic literature review. Career-related concerns are an issue even within student population. Previous researches have aimed to explore students’ career anxiety but there has not been any literature review that concludes these findings. Objectives: This study aims to systematically review existing researches to find out how career-related anxieties have been identified and what might predict them. Methods: From 780 articles found, 17 articles were considered eligible in which information such as definition, measurement methods, and correlates were then extracted. Findings: Students’ career anxiety is generally defined in terms of feelings, physiological reactions, and cognitive components related to students’ career situations. Factors related to individuals, their environment, and helpful environmental and psychological resources were identified. Conclusion: Students’ career anxiety might manifest itself in negative feelings, physiological reactions, and maladaptive cognitive state. School and students’ direct environment might play an essential role in ensuring smooth career exploration by identifying and helping manage students’ career anxiety. Keywords: students’ career anxiety, students’ employment anxiety, career-related anxietyDOI: http://dx.doi.org/10.23960/jpp.v13.i3.202335